A mitochondrial tRNAMet mutation causing developmental delay, exercise intolerance and limb girdle phenotype with onset in early childhood. (January 2015) - Born, Alfred Peter; Duno, Morten; Rafiq, Jabin; Risom, Lotte; Wibrand, Flemming; Østergaard, Elsebet; Vissing, John
Abstract A 10-year-old girl presented with exercise intolerance, learning difficulty, and muscle weakness in a limb girdle distribution. She had delayed achievement of motor milestones and difficulties with social interaction at pre-school age. Muscle biopsy showed no myopathic or dystrophic features, but 90% COX negative fibres and ragged blue fibres. Respiratory chain enzyme analysis in muscle showed a combined deficiency and mitochondrial DNA sequencing revealed the presence of an m.4450G>A mutation in the MT-TM gene encoding the tRNA for methionine. The mutation was only detected in mtDNA extracted from muscle and skin fibroblast, and could not be found in other tissues or in the mother. This is the second patient reported in the literature with a mitochondrial myopathy due to a mt-tRNAMet mutation. The first patient, a 30-year-old woman, presented with exercise intolerance, limb girdle muscle weakness, lactic acidosis, learning difficulty, and growth retardation in early childhood. Thus, the two patients exhibit strikingly overlapping phenotypes.